Discovery of Novel Saponins from the Viscera of the Sea Cucumber Holothuria lessoni - Yadollah Bahrami; Wei Zhang; Chris Franco (Marine Drugs, 2014)
Sea cucumbers, sometimes referred to as marine ginseng, produce numerous compounds with diverse functions and are potential sources of active ingredients for agricultural, nutraceutical, pharmaceutical and cosmeceutical products. We examined the viscera of an Australian sea cucumber Holothuria lessoni Massin et al. 2009, for novel bioactive compounds, with an emphasis on the triterpene glycosides, saponins. The viscera were extracted with 70% ethanol, and this extract was purified by a liquid-liquid partition process and column chromatography, followed by isobutanol extraction. The isobutanol saponin-enriched mixture was further purified by high performance centrifugal partition chromatography (HPCPC) with high purity and recovery. The resultant purified polar samples were analyzed using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS)/MS and electrospray ionization mass spectrometry (ESI-MS)/MS to identify saponins and characterize their molecular structures. As a result, at least 39 new saponins were identified in the viscera of H. lessoni with a high structural diversity, and another 36 reported triterpene glycosides, containing different aglycones and sugar moieties. Viscera samples have provided a higher diversity and yield of compounds than observed from the body wall. The high structural diversity and novelty of saponins from H. lessoni with potential functional activities presents a great opportunity to exploit their applications for industrial, agricultural and pharmaceutical use.